Restricted and repetitive behaviours - Leekam, Sue; Prior, Margot (Henry Stewart Talks, 2010)
Phenomenology, Description of restricted and repetitive behaviours (RRBs), Structure and sub-grouping, Distinctiveness from other neurodevelopmental disorders, Cause, Developmental origins, Underlying cognitive mechanisms, Triggers and functions, Potential for change, Change with age and development, Change with intervention, Conclusions and recommendations